Chemical partitioning and DNA fingerprinting of some pistachio (Pistacia vera L.) varieties of different geographical origin. (April 2019) - Mannino, Giuseppe; Gentile, Carla; Maffei, Massimo E.
Abstract: The genus Pistacia (Anacardiaceae family) is represented by several species, of which only P. vera L. produces edible seeds (pistachio). Despite the different flavor and taste, a correct identification of pistachio varieties based on the sole phenotypic character is sometimes hard to achieve. Here we used a combination of chemical partitioning and molecular fingerprinting for the unequivocal identification of commercial pistachio seed varieties (Bronte, Kern, Kerman, Larnaka, Mateur and Mawardi) of different geographical origin. The total phenolic content was higher in the variety Bronte followed by Larnaka and Mawardi cultivars. The total anthocyanin content was higher in Bronte and Larnaka varieties, whereas the total proanthocyanidin content was higher in Bronte, followed by Mawardi and Larnaka varieties. HPLC-DAD-ESI-MS/MS analyses revealed significant (P < 0.05) higher amounts of cyanidin-3-glucoside, idein, eryodictol-7-galactoside, quercetin-3-glucoside, luteolin-glucoside and marein in the variety Bronte, whereas higher amounts of peonidin-3-glucoside, okanin 4′-galactoside, hyperoside and quercetin-4′-glucoside were found in the variety Larnaka. The highest content of catechin was found in the Mawardi variety. A significantly (P < 0.05) higher total amount of fatty acids was found in the varieties Mateur, Kern and Bronte, followed by the varieties Larnaka and Mawardi, whereas the variety Kerman showed the lowest total fatty acid content. GC-FID and GC-MS analyses revealed the presence of several polyunsaturated fatty acids. Kern and Mateur varieties showed a significantly (P < 0.05) higher amount of linoleic acid, whereas the variety Bronte showed the highest amount of oleic acid. Molecular fingerprinting was achieved by ITS DNA PCR-RFLP analysis. Three different restriction enzymes ( Rsa I, TaqαI and Pst I) were used to selectively cleave the resulting amplicons. A TaqαI site could be selectively found in the varieties Kerman, Larnaka and Mateur, whereas the digestion of the PCR products by Rsa I gave specific patters exclusively on Bronte and Mawardi. Digestion by Pst I gave specific patters exclusively on the Kern variety. The results showed that the Mediterranean varieties (Mateur, Bronte and Larnaka) show similar chemical patterns and (particularly for Mateur and Larnaka) a close phylogenetic relationship, allowing a chemical and molecular partitioning with respect to the other varieties. Graphical abstract: Phenolic compounds, fatty acids and ITS DNA-fingerprinting successfully discriminate pistachio varieties of different geographical origin.Image 1 Highlights: Pistacia vera varieties show quantitative and qualitative differences in phenolic compounds. Fatty acid compositions reveal similar quality and differential content in P. vera varieties. The chemical partitioning of P. vera allows the discrimination of the geographical origin. Identification of sites of PCR-RFLP in the DNA genome allows P. vera DNA fingerprinting. Biomolecular and chemical data discriminate P. vera varieties of different geographical origin.